Low S-allele numbers limit mate availability, reduce seed set and skew fitness in small populations of a self-incompatible plant - Young, Andrew G.; Pickup, Melinda (The Journal of applied ecology, 2010)
1. The role of genetic factors in species decline and extinction is the subject of a long-running controversy, with demographical factors often seen as more important for the immediate persistence of populations and species. One gene system that directly links genetic diversity with reproduction, through its influence on fertilization success, is the self-incompatibility (SI) locus in angiosperm plants. Despite the potential importance of SI allele diversity for demographical function, there are few direct measures of S-allele numbers in multiple populations, and no studies have simultaneously measured reproductive output, mate availability, S-allele diversity and pollinator service. 2. We used diallel crosses to estimate S-allele number and mate availability in seven populations of the forb Rutidosis leptorrhynchoides ranging in size from 5 to 100 000 plants. Seed set and correlated paternity were assessed from open-pollinated inflorescences to examine reproductive output and variance in female and male fitness. To assess whether populations were receiving adequate pollinator service, the amount of pollen deposited on open-pollinated stigmas was quantified. 3. We found that small populations (<100 plants) of R. leptorrhynchoides have low S-allele diversity and mate availability and exhibit significant reductions in seed set relative to large populations (>1000 plants) with higher numbers of S-alleles, despite the maintenance of pollinator service. Greater variance in seed set among plants and higher correlated paternity in small populations suggest that low S-allele numbers are directly limiting mate availability and causing the observed reproductive failure. 4. Synthesis and applications. Our work demonstrates that the loss of genetic diversity at the SI locus can have immediate detrimental effects on reproductive performance, despite the maintenance of pollinator service. These results highlight the importance of genetic factors in determining demographical outcomes when clear links between genotype and individual fitness exist, even when populations are not ecologically constrained. This result is important for the conservation and management of many plant species as approximately half of all angiosperm families contain species with genetically controlled SI and the loss of genetic diversity through habitat loss and fragmentation is an ever-increasing reality for plant species worldwide.